Tabooed Terrain: Reflections On Conducting Adult Education Research In Lesbian/Gay/Queer Arenas - Kathleen Edwards; Andre Grace; Brenda Henson; Wanda Henson; Robert J. Hill; Ed. Taylor (Adult Education Research Conference, 1998)
Introduction: The issues to be explored in this symposium are the multiple ways that same-sex orientation is negotiated and mediated in Adult Education research. The sociology of learning and other diverse bodies of literature (e.g. gay/queer theory) show that, in the main, same-sex orientation (matter related to Lesbians, Gay men, Transgendered, Bisexuals and Transsexuals) is treated as tabooed terrain in both the academy and society (Hill, 1995), often with grave results. In this symposium, panelist Andre Grace positions his early developmental denial of queer being and acting as a form of self-mutilation. Andre has taken up a self-directed project of autobiographical writing and theorizing as a means to subvert society’s forbidden parameters. Since many educators and community members fall back on stereotypes, internalized homophobia and homoprejudice that flagrantly compromise the very principles for which they labor (Harbeck, 1997), Andre has learned to name and express his outlawed self.